128TiP VCN-01 plus durvalumab in subjects with recurrent/metastatic head & neck squamous cell carcinoma (R/M HNSCC): Phase I clinical trial. (15th December 2019) - Jove, M; Braña, I; Taberna, M; Hernando-Calvo, A; Castro, J Brenes; Garralda, E; Serrahima, M Plana; Pujol, M Maños; Capella, G; Alemany, R; Blasi, E; Blasco, C; et al.
Abstract: Background: VCN-01 is an oncolytic adenovirus with replication restricted to cells with a nonfunctional retinoblastoma pathway. Upon selective replication VCN-01 expresses the matrix remodeling-enzyme hyaluronidase to enhance virus spreading and tumor uptake of different therapeutics, including immune check-point inhibitors. In a phase I performed in pancreatic carcinoma VCN-01 reached tumors after systemic administration and induced CD8-infiltration, tumor inflammation and PD-1/PD-L1 up-regulation. We hypothesize these intratumor effects may help to overcome the observed resistance to Durvalumab and other PD-(L)-1 checkpoint inhibitors Trial Design: NCT03799744 is a multi-center, open-label dose-escalation phase I study evaluating the safety, tolerability and efficacy of the combination of VCN-01 plus durvalumab in R/M HNSCC patients who have progressed on prior PD-(L)-1 checkpoint inhibitors. Patients need to have neutralizing antibodies levels against adenovirus ≤1/350 dilution to be included. The study follows a 3 + 3 design with two dose levels for VCN-01 (3, 3.10 12 & 1.10 13 vp) combined with Durvalumab at a fixed dose of 1500mg intravenous (i.v.). Two treatment arms are explored: I) Concomitant single i.v. dose of VCN-01 with durvalumab on cycle 1 day 1 followed by durvalumab Q4W; II) Sequential single i.v. VCN-01 on cycle 1 day -14 plus durvalumab on cycle 1 day 1 followed by durvalumab Q4W. Patients continue durvalumab Q4W until disease progression, unacceptable toxicity or withdrawal of consent. The primary objective of the study is to evaluate the safety and tolerability of VCN-01 with durvalumab in the two regimens of administration and to establish the recommended phase II dose. Secondary objectives are progression free survival, overall response rate by irRECIST /RECIST, VCN-01 pharmacokinetics and shedding in blood. Other exploratory biomarkers will be analyzed in tumor biopsies (immune markers), serum (hyaluronidase levels), stool (microbiome) and imaging (dynamic contrast-enhanced MRI, diffusion weighted imaging and T2 mapping). The study opened recruitment in April 2019 with 7 out of 18 planned patients enrolled at time of submission. Clinical trial identification: NCT03799744. Legal entity responsible for the study: Catalan Institute of Oncology (ICO). Funding: VCN Biosciences, AstraZeneca. Disclosure: M. Jove: Advisory / Consultancy: Boehringer Ingelheim. I. Braña: Advisory / Consultancy, Research grant / Funding (self): Orion Pharma; Speaker Bureau / Expert testimony, Research grant / Funding (self): Bristol-Myers Squibb; Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: AstraZeneca; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Merck Serono; Research grant / Funding (self): Celgene; Research grant / Funding (self): Gliknik; Research grant / Funding (self): GSK; Research grant / Funding (self): Janssen; Research grant / Funding (self): KURA; Research grant / Funding (self): MSD; Research grant / Funding (self): Novartis; Research grant / Funding (self): Pfizer; Research grant / Funding (self): Shattuck; Research grant / Funding (self): Northern Biologics; Research grant / Funding (self): Rakutan Aspirian; Research grant / Funding (self): Naobiotics. M. Taberna: Honoraria (self), Advisory / Consultancy, Non-remunerated activity/ies: Merck; Honoraria (self), Non-remunerated activity/ies: AstraZeneca; Honoraria (self): Bristol-Myers Squibb; Advisory / Consultancy: Nanobiotics. E. Garralda: Leadership role, Research grant / Funding (institution): Novartis; Leadership role: Principia Biopharma Inc; Leadership role: Lilly, S.A; Advisory / Consultancy, Leadership role: Roche / Genentech Inc; Leadership role: Loxo Oncology Inc; Advisory / Consultancy, Leadership role: F.Hoffmann La Roche Ltd; Leadership role: Symphogen A/S; Speaker Bureau / Expert testimony, Leadership role, Travel / Accommodation / Expenses: MSD; Leadership role: Incyte; Leadership role: Pharma Mar; Leadership role: Kura Oncology; Leadership role: Macrogenics; Leadership role, Travel / Accommodation / Expenses: Glycotope; Leadership role: Pierre Fabre; Leadership role: Cellestia Biotech; Leadership role, Travel / Accommodation / Expenses: Menarini Ricerche; Leadership role: Blueprint Medicines; Leadership role: Beigene; Leadership role: Sierra Oncology; Leadership role: Genmab; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Bristol-Myers Squibb; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Janssen Global Services ; Advisory / Consultancy: Ellipses Pharma; Advisory / Consultancy: NeoMed Therapeutics; Advisory / Consultancy: SeaGen; Speaker Bureau / Expert testimony: ThermoFisher. G. Capella: Advisory / Consultancy, Shareholder / Stockholder / Stock options: VCN Biosciences. R. Alemany: Advisory / Consultancy, Shareholder / Stockholder / Stock options: VCN Biosciences; Research grant / Funding (institution): Lokon Pharma; Research grant / Funding (institution): Mologen. E. Blasi: Full / Part-time employment: VCN Biosciences. C. Blasco: Full / Part-time employment: VCN Biosciences. M. Cascallo Piqueras: Leadership role, Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: VCN Biosciences. R. Mesia Nin: Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony: Merck Serono; Advisory / Consultancy, Speaker Bureau / Expert testimony: MSD; Advisory / Consultancy, Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Advisory / Consultancy: Sanofi; Advisory / Consultancy: Nanobiotix; Advisory / Consultancy: Bayer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche. All other authors have declared no conflicts of interest.